Nacionalna raziskovalna infrastruktura Središča ELIXIR-SI - Leskošek, Branimir (Informatica Medica Slovenica, 2024)
The Cohesion Infrastructure Project ELIXIR-SI RI-SI-2 has facilitated the upgrade of the national research infrastructure (RI) ELIXIR-SI for the life sciences. The RI of ELIXIR-SI Centre (https://elixirslovenia.org) now comprises (1) a national data node for the life sciences, (2) a central laboratory for nextgeneration sequencing and a laboratory for single-cell analyses, and (3) an education centre focusing on data management, bioinformatics, and laboratory workflows. Various laboratory and bioinformatic analyses are conducted using appropriate tools and services. We have optimized all steps of multiple experimental workflows (sample acquisition, laboratory work preparation and execution, quality control, bioinformatic analysis). The generated data adhere to the principles of open science and FAIR, thus facilitating their improved utilisation. The RI of ELIXIR-SI Centre is suitable for fundamental and applied research, educational courses, student exercises, and practical work within research, undergraduate, graduate, and doctoral projects. It is part of the European ELIXIR network (https://elixir-europe.org). In this article, we present a study on the utilisation of the RI ELIXIR for the purpose of publishing research articles.
Keywords: bioinformatics; bioinformatika; data management; ravnanje s podatki; raziskovalna infrastruktura; research infrastructure; Slovenia; Slovenija